The Auxin-Response Repressor IAA30 Is Down-Regulated in Reproductive Tissues of Apomictic Paspalum notatum - Siena, Lorena Adelina (2022)
The capacity for apomixis in Paspalum notatum is controlled by a single-dominant genomic region, which shows strong synteny to a portion of rice chromosome 12 long arm. The locus LOC_Os12g40890, encoding the Auxin/Indole-3-Acetic Acid (Aux/IAA) family member OsIAA30, is located in this rice genomic segment. The objectives of this work were to identify transcripts coding for Aux/IAA proteins expressed in reproductive tissues of P. notatum, detect the OsIAA30 putative ortholog and analyze its temporal and spatial expression pattern in reproductive organs of sexual and apomictic plants. Thirty-three transcripts coding for AUX/IAA proteins were identified. Predicted protein alignment and phylogenetic analysis detected a highly similar sequence to OsIAA30 (named as PnIAA30) present in both sexual and apomictic samples. The expression assays of PnIAA30 showed a significant down-regulation in apomictic spikelets compared to sexual ones at the stages of anthesis and post-anthesis, representation levels negatively correlated with apospory expressivity and different localizations in sexual and apomictic ovules. Several PnIAA30 predicted interactors also appeared differentially regulated in the sexual and apomictic floral transcriptomes. Our results showed that an auxin-response repressor similar to OsIAA30 is down-regulated in apomictic spikelets of P. notatum and suggests a contrasting regulation of auxin signaling during sexual and asexual seed formation.